A Comparative Assessment of Stress Levels between Initial and Final Year MBBS Hostel Residents of a private medical college in Lahore - Ismail Mazhar, Qudsia Umaira Khan, Nouman Asad, Hunniya Bint E Riaz, Khawaja Haider Sami, Aiza Faisal Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find the emotional and environmental stress in hostel resident medical students. Methods: The undertaken cross-sectional comparative study aims to identify and compare the responses of final and initial (2nd year) year medical students living in hostel in a private medical college in Lahore to environmental and emotional stress through a structured questionnaire. The 125 responses were analyzed through SPSS. Results: Stress of two types faced by medical hostel students were analyzed in the study. The study showed that responses ranged from lack of medical facilities to hostel rules in environmental stress and disloyalty to extra burden of study activities in emotional stress. A comparison of responses showed that there was no significant difference between males and females as both faced similar environmental and emotional stress. Further, analysis depicted that initial-year hostellers were more sensitive to both types of stress as compared to final-year medical hostellers. Thus, finally, the results highlighted that emotional factors caused more stress as compared to environmental factors. Practical implication: The study would help the students with an insight, realization, and identification of situations that could cause stress during hostel life experiences. This understanding could be helpful in overcoming the issues before they cause emotional or environmental stress, thus developing the capacity to cope in a productive manner. Further, this study would be helpful in arranging and providing professional mentoring. Conclusion: It is concluded that stress is unavoidable and is likely to be experienced by medical students residing in hostels. The study focused on stress caused by environment and emotions. The results of the study suggest that it was important to realize and identify stress-causing situations for students to focus on study challenges with a healthy mind and body. Keywords: Medical students, hostel, stress, psychological stress, mental health